Temporomandibular dysfunction association with psychological factors: a literature review (Research, Society and Development, 2021)
Therefore, this study aimed to review the literature focusing on the relationship between TMD and psychological factors. This is a literature review with a qualitative approach. The databases were PubMed and Bireme, from 2008 to 2018. As inclusion criteria: articles published in the English language, with the descriptors "temporomandibular Joint disorder", "anxiety", "depression", "stress’‘ and ''psychological”. Articles of literature review and articles where the psychological component was only cited and not evaluated were excluded. Eight articles were characterized, of which the results pointed out the significant correlation between psychosocial, somatic and behaviour comorbidities. Psychological factors such as somatization, depression, anxiety and distress, mainly related to the female gender, have a significant impact on the prevalence of TMD. It is noted that there is a relation to the cites factors. In this regard, it requires the interdisciplinary assistance due to the physical-psychological nature, in other words, participation of psychology to intensify the dental treatment.